Differential effects of Roux-en-Y gastric bypass surgery and vertical sleeve gastrectomy on fatty acid levels - Sarkar, Sudipa (Obes Surg, 2019)
BACKGROUND: Bariatric surgery affects lipid levels; however, no comparison of the effects of Roux-en-Y gastric bypass surgery (RYGB) versus vertical sleeve gastrectomy (VSG) on serum fatty acid levels exists in the current literature. The present post-hoc study describes the effects of RYGB and VSG on serum fatty acid levels at 6 months and 18 months post treatment, compared to a control group. METHODS: The study participants, all of whom were women, had blood drawn at baseline, 6 months, and 18 months after treatment. Serum fatty acid data were available for 57 participants at baseline, 57 participants at 6 months, and 43 participants at 18 months post-treatment. RESULTS: Compared to baseline, serum non-esterified fatty acids (NEFA) levels were significantly higher at 6 and 18 months in the VSG group compared to the RYGB group. In the RYGB group, all three of the measured saturated fatty acids (SFAs), two of the three measured monounsaturated fatty acids (MUFAs), and two of the three measured polyunsaturated fatty acids (PUFAs) were decreased at 6 and 18 months compared to baseline, although not all of these changes were significant compared to the control and VSG groups. On the other hand, one of the three MUFAs and two of the three PUFAs were increased at 6 and 18 months in the VSG group, although these changes were not all significant compared to the control and RYGB groups. Significant positive associations were noted between change in body mass index (BMI) and two of the SFAs and one of the MUFAs. Similarly, significant positive associations were noted between change in HOMA-IR and 3 of the measured fatty acids. CONCLUSIONS: At 6 and 18 months after VSG, a significant increase in NEFAs was seen, compared to RYGB. Reductions in all measured SFAs and most measured MUFAs and PUFAs at 6 and 18 months post RYGB were seen, although not all of these decreases were significant when compared to the control and VSG groups. Similarly, increases in most of the PUFAs at 6 and 18 months were observed after VSG, although not all of these changes were significant when compared to the other treatment groups. Changes in BMI and HOMA-IR were significantly associated with changes in some but not all fatty acids.